Survey to measure the quality of life of patients with tuberculosis in Alexandria, Egypt: a cross-sectional study - Esraa Abdellatif Hammouda; Wahib Fayez Gobran; Reem Mohamed Tawfeek; Ola Fahmy Esmail; Rasha Ashmawy; Naglaa Youssef; Ramy Mohamed Ghazy (BMC, 2023)
Abstract Background Assessment of quality of life (QoL) in patients with tuberculosis (TB) may improve healthcare providers' understanding of the disease burden. This study aimed to investigate the QoL of patients with TB in Alexandria, Egypt. Methods This cross-sectional study was conducted in chest clinics and main chest hospitals in Alexandria, Egypt. A structured interview questionnaire was used to collect data from participants through face-to-face interviews from November 20, 2021, until the June 30, 2022. We included all adult patients aged 18 years or above during the intensive or continuation phase of treatment. The World Health Organization (WHO) WHOQOL-BREF instrument was used to measure QoL, which includes the physical, psychological, social relationships, and environmental health domains. Using propensity score matching, a group of TB free population was recruited from the same setting and completed the questionnaire. Results A total of 180 patients participated in the study: 74.4% were males, 54.4% were married, 60.0% were 18-40 years old, 83.3% lived in urban areas, 31.7% were illiterate, 69.5% reported insufficient income, and 10.0% had multidrug-resistant TB. The TB-free population group had higher QoL scores than the TB patients' group: (65.0 ± 17.5 vs. 42.4 ± 17.8) for the physical domain, (59.2 ± 13.6 vs. 41.9 ± 15.1) for the psychological domain, (61.8 ± 19.9 vs. 50.3 ± 20.6) for the social domain, (56.3 ± 19.3 vs. 44.5 ± 12.8) for the environment domain, (4.0(3.0-4.0) vs. 3.0(2.0-4.0)) for general health, and (4.0(3.0-4.0) vs. 2.0(2.0-3.0)) for the general QoL, P < 0.0001. Patients with TB aged 18-30 years had the highest environmental score compared with the other age groups (P = 0.021). Conclusions TB had a significant negative impact on QoL, with the physical and psychological domains being the most affected. This finding necessitates strategies to improve QoL of patients with to enhance their compliance to treatment.